Splicing of Friend Murine Leukemia Virus env-mRNA Enhances Its Ability to Form Polysomes - Machinaga, Akihito; Ishihara, Syuhei; Shirai, Akiko; Takase-Yoden, Sayaka (Frontiers in Microbiology, 2016)
Friend murine leukemia virus (MLV) belongs to the gamma retroviruses of the Retroviridae family. The positive-sense RNA of its genome contains a 5’ long terminal repeat (LTR), 5’ leader sequence, gag, pol, env, and 3’ LTR. Transcription from proviral DNA begins from the R region of the 5’ LTR and ends at the polyadenylation signal located at the R region of the other end of the 3’ LTR. There is a 5’ splice site in the 5’ leader sequence and a 3’ splice site at the 3’ end of the pol region. Both full-length unspliced mRNAs and a singly spliced mRNA (env-mRNA) are produced in MLV-infected cells. The MLV Env protein plays important roles both in viral adsorption to host cells and in neuropathogenic disease in MLV-infected mice and rats. Understanding the regulatory mechanisms controlling Env expression is important for determining the functions of the Env protein. We have previously shown that splicing increases env-mRNA stability and translation efficiency. Generally, mRNA polysome formation correlates with translation efficiency. Therefore, here we investigated the effects of env-mRNA splicing on polysome formation to identify mechanisms for Env up-regulation due to splicing. We performed polysome profile analyses using Env-expression plasmids producing spliced or unspliced env-mRNA and showed that the former formed polysomes more efficiently than the latter. Thus, splicing of env-mRNA facilitated polysome formation, suggesting that this contributes to up-regulation of Env expression. We replaced the env region of the expression plasmids with a luciferase (luc) gene, and found that in this case both unspliced and spliced luc-mRNA formed polysomes to a similar extent. Thus, we conclude that whether mRNA polysome formation is affected by splicing depends on the structure of gene in question.